Airline economics in Asia - Fu, Xiaowen; Peoples, James (Advances in airline economics, 2018)
Covers low-cost carrier growth in Japan, competition against full service hub carriers in the Middle East, aviation market liberalization in Central Asia, high-speed-rail and airline competition in China, air transport and tourism in Asia and Australia, airline performance and outsourcing, airports development, and airport-airline cooperation.